Allelic diversity of butyrophilin (BTN1A1) gene in Indian bovines - Manoj Kumar; Poonam Ratwan; Ramendra Das; Alka Chopra; Vikas Vohra (Indonesian Journal of Biotechnology, 2017)
Indian milch bovines comprises of 58.56% of total livestock population (512.05 million) in the country and primarily includes native and crossbred cattle (37.28%) and water buffaloes (21.28%). Milk and milk products are essential food items of Indian diet especially in children, old and senile. Milk fat is an important constituent of milk and has an economic value and its percentage in milk varies betweem species and breeds within species. Butyrophilin (BTN1A1) a membrane protein regulates secretion of lipids and size of a fat globule in milk. Present study was conducted in 538 bovines of 11 breeds/populations adapted to different parts of India, with an aim to screen and determine the major allele of BTN1A1 gene using PCR-RFLP based test. Results indicate that exon 8 of BTN1A1 gene is polymorphic in Tharparkar, Sahiwal, Jhari and Belahi populations of native cattle and Holstein Friesian and Jersey crossbreds where as the same exon was monomorphic in Murrah, Chilika, Gojri, Chhattisgarhi and Bargur populations of water buffalo. We conclude that variations in BTN1A1 gene can serve as an excellent genetic marker while selecting cows for higher milk fat and can be applied while formulating their breeding plans.